İki Farklı Polimerden Simultane Olarak Elektrospinning Yöntemiyle Nanolif Ve Membran Üretimi - Güçlü, Serkan (Fen Bilimleri Enstitüsü, 2012)
Son yıllarda çevre mühendisliği alanında membran filtrelerin kullanımı oldukça artmıştır. Membran filtreler sayesinde konvansiyonel sistemlere göre daha az yer kaplayan, işletmesi daha kolay olan ve daha iyi giderme verimleri ile çalışan sistemlerin inşası mümkün olmuştur. Bu teknoloji güvenilir ve verimli bir teknoloji olarak evsel ve endüstriyel atıksu uygulamalarında diğer rakiplerine karşı gayet yeterli bir alternatif sunmaktadır. Ancak membran teknolojilerinin önündeki en büyük limit maliyetlerdir. Membranların ilk yatırım ve işletme maliyetleri konvansiyonel sistemlere göre fazladır. İşletme ve ilk yatırım maliyetini düşürmek için daha düşük yüzey alanından daha yüksek akı geçirebilen yani permabilitesi daha yüksek ve porozitesi daha fazla olan membranlara ihtiyaç vardır. Bu yüksek performanslı membranları üretebilmek için membran üretimi alanında pek çok çalışma yapılmaktadır. Bu çalışma alanlarından birisi elektrospinning yöntemi ile nanofiber membran üretilmesidir. Bu çalışmanın amacı iki farklı polimerin simultane olarak aynı toplayıcı plaka üzerinde toplanması ile nanofiber membran elde edilmesidir. Tez kapsamında kullanılan polimerlerden olan poliakrilonitrilden üretilen nanofiber membranlar 0,7-0,8 mikron gibi düşük por çapı özelliğine sahiptir. Polisülfon polimerinden üretilen nanofiber membranları ise 1,3-1,5 mikron ile PAN polimerinden daha yüksek por çapına sahiptir. Polisülfon polimeri 180-190°C civarında erime özelliğine sahiptir. Ayrıca polisülfon polimeri ile üretilmiş nanofiber membranlar bu sıcaklık civarında muamele edildiğinde lifler birbirine yapışmakta ve mekanik dayanıklılık artmaktadır. PAN polimeri ile oluşturulmuş nanofiber membranların mekanik mukavemetini arttırmak için ise 270-300°C sıcaklıklarda işlem uygulamak gerekmektedir. Görüldüğü üzere, PAN polimerinden oluşturulmuş nanofiber membranlar PSU ile oluşturulmuş nanofiber membranlara göre daha düşük por çapı özelliklerine sahipken PSU ile oluşturulmuş nanofiber membranlar PAN ile oluşturulmuş nanofiber membranlara göre daha düşük sıcaklıklarda mekanik dayanım kazandırılabilme özelliğine sahiptir. Simultane spinning ile oluşturulmuş nanofiber membranda iki polimerin birbirine üstün bu iki özelliği bir arada kullanılmak istenmektedir. Üretilen membranlarda por çapını poliakrilonitril, dayanıklılığı ise polisülfon belirlemiştir. Deneysel çalışma 3 adımdan oluşmaktadır. İlk adımda, polisülfon, dimetilformamid, metilpirolidon ve tuz içeren çözelti elektrospinning işlemi için optimize edilmiştir. 2. adımda poliakrilonitril çözeltisi optimize edilirken 3. Adımda bu her iki polimerin simultane elektrospinning işlemi optimize edilmiştir. Üretilen nanofiber membranların taramalı elektron mikroskobu görüntülerine bakılmış ve por çapı analizleri yapılmıştır. Bu çalışmaların sonunda her birinin performansı karşılaştırılmıştır. Performans testleri için Ataköy ileri biyolojik arıtma tesisinden alınan aktif çamur örneği ile İTÜ göletinden alınan göl suyu kullanılmıştır.

In recent years researcher’s interest is focused on membrane production with the method of electrospinning and plenty of research articles were published. Concisely Electrospinning is nano sized fiber production from a synthetic or natural polymer through high voltage. Polymeric membranes, which are used in water treatment, are extensively produced with the method of phase inversion. Membranes produced through conventional techniques such as phase inversion shows low flux ratios depend on the distribution and geometric structures of pores. Nanofibers produced with the method of Electrospinning has very high porosity. All spaces are connected to each other and generally have the porosity of around 80%. In consequence of this connected pore structures insure better permeability than the conventional membranes. Likewise, electrospun membrane production is cheaper than other conventional methods. As a commercial membrane production cost is around 50 €/m2, the estimated cost of membranes manufacturing with nanofibers are a around 20 €/m2. Scientists carry out a lot of researches with different polymers for nanofiber membrane production. The aim of this study is to manufacture the nanofiber membrane as simultaneously collecting the different polymer nanofibers on same collection layer using two different polymer solutions. The nanofiber membranes produced with PAN polymer showed lower pore size characteristics than polysulphone nanofiber membranes. It was about 0,7-0,8 µm while PSU nanofiber membrane pore sizes were 1,3-1,5 µm. For better stability and strength of nanofiber membranes, it is commonly used heat treatment. After checking DSC curves in literature, it is observed that the needed heat for PSU nanofiber membrane treatment was 180-190°C and for PAN nanofiber membrane treatment 270-300°C. In this work, in the simultaneously produced nanofiber membrane, while the PAN is determining the pore size, the strength and stability is provided by PSU. So a lower pore size containing nanofiber membrane with better stability is provided first time using simultaneous electrospinning technique. If PAN nanofiber were used stand alone, it would needed more energy (270-300°C) than PSU (180-190°C). So with simultaneous electrospinning technique the stability and strength is provided with lower energy. Methyl pyrollidone and dimethyl formamide is used as solvent, polysulphone and polyacrylonitrile (PAN) is used as polymer. PAN is dissolved in dimethyl formamide in concentration of % 6. Polysulphone is dissolved in mixed dimethyl formamide and methyl pyrollidone in concentration of %17. A little amount of salt is added to polysulphone solution. First nanofiber membranes are produced individually as polysulphone nanofiber membrane and polyacrylonitrile nanofiber membrane. The production parameters are noted for each membrane. Polyacrylonitrile nanofiber membrane production was easier than polysulphone nanofiber membrane. Polysulphone nanofiber membrane could be optimized after 17 experiment. Two problem was observed during electrospinning. Some nanofiber membranes were wet. Because the solvent were not evaporated well during electrospinning jet. To dissolve this problem, it was changed the amounts of methyl pyrollidone and dimethyl acetamide. Dimethyl acetamide has lower density than dimethyl formamide. So it can evaporate more easily than methyl pyrollidone. But this time the problem was congealing of polymers on nozzles. Solvents was evaporating rapidly and polymers congealed. To dissolve this problem, the amount of methyl pyrollidone and dimethyl acetamide is optimized. Also small amount of salt is added to improve electrical features of polymer solution. PAN nanofiber membrane is producted easily. After producing nanofiber membranes it is applied heat treatment 5 hour long with 185°C. Porosity, permeability, wastewater and lake water filtration performances were determined and compared for each of it. For comparing nanofiber membrane performances with phase inversion membranes is selected Microdyn Nadir MV020 phase inversion membranes. Fiber sizes or nanofiber membrane thicknesses also examined via SEM analysis.. Distilled water fluxes of three membranes are examined. Distilled water fluxes are for MV020 is 156 l/m2.sa, for heat treated nanofiber membrane 1605 l/m2.sa and for non-heat treated nanofiber membrane 1302 l/m2.sa under 0,2 Bar pressure. As seen, nanofiber membrane fluxes are higher than MV020. This is because, nanofiber membranes have bigger pores and bigger porosity. Also all of the pores in nanofiber membranes are connected each other. For wastewater filtration performance tests, wastewater is taken from Atakoy Advanced Biological Wastewater Treatment Plant. In wastewater filtration heat treated nanofiber membrane showed better structural strength than non-heat treated nanofiber membrane. Non-heat treated nanofiber membrane is teared and scattered while heat treated nanofiber membrane keeps its structural unity. For three membrane, suspended solid removal rate was higher than %99. But MV020 membrane showed better flux rate than others. Nanofiber membrane fluxes are decreased logarithmically and are fixed for MV020 41 l/m2.sa, for heat treated nanofiber membrane 20 l/m2.sa, for non-heat treated nanofiber membrane 15 l/m2.sa under 0,2 Bar pressure. For lake water filtration performance tests, lake water is taken from Istanbul Technical University Ayazaga Campus pond. Lake water filtration fluxes are for MV020 is 39 l/m2.sa, for heat treated nanofiber membrane 146 l/m2.sa and for non-heat treated nanofiber membrane 222 l/m2.sa under 0,2 Bar pressure In lake water filtration, suspended solids removal rates are very efficient for both 3 membranes. Raw lake water turbidity is 3,68 NTU. After filtration, turbidities are for heat treatment membrane 0,45 NTU, for non-heat treatment membrane 0,58 NTU and for MV020 membrane is 0,49 NTU. Turbidity removal is more efficient for heat treated nanofiber membrane. In total organic carbon removal, membranes are not efficient. While inlet TOC value is 20,04 mg/l, after MV020 membrane filtration it is 17,08 mg/l, after non-heat treated nanofiber membrane 20,06 mg/l and after heat treated nanofiber membrane 20,52 mg/l. UV absorbance values are better with MV020 membrane, but results are very similar each other. In wastewater filtration nanofiber membranes showed good rejection rates but they have flux decline problem depending on biofouling. After solving this biofouling problem, nanofiber membranes can be a good alternative for commercial phase inversion membranes. In lake water filtration, best flux values are obtained with nanofiber membranes. Rejection rates were also efficient. So, the nanofiber membrane produced with simultaneously electrospinning of 2 polymers is an alternative for lake and surface water filtration applications.
Nanofiber And Membrane Production Using Two Polymers With Simultaneous Electrospinning Technique
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: elektrospinning; polisülfon; poliakrilonitril; nanofiber; membran; membran filtrasyonu; electrospinning; polysulphone; polyacrylonitrile; nanofiber; membrane; membrane filtration